URGENSI PENYELESAIAN KASUS BANTUAN LIKUIDITAS BANK INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 10 TAHUN 1998 TENTANG PERBANKAN (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 1555K/PID.SUS/2019) - Aldo Evander Wijaya; Jeane Neltje Saly (Fakultas Hukum Universitas Tarumanagara, 2021)
The BLBI case is indeed quite complex to handle, considering that there were two BPK audit results in 2006 and 2017 with different results, especially regarding the presence or absence of state financial losses as an element of corruption. The problem faced is how the impact of uncertainty in rescuing the BLBI case on the future of investment in Indonesia and how urgency to resolve the Bank Indonesia Liquidity Assistance case based on Law Number 10 of 1998 concerning Banking related to the Supreme Court's Decision Number 1555 K/Pid.Sus/2019. The research method used in writing this scientific paper is a normative juridical research method. The results of the study indicate that the impact of uncertainty in rescuing the BLBI case on the future of investment in Indonesia is investor distrust of the investment climate in Indonesia, given the long-winded and time-consuming BLBI settlement. The urgency of resolving the Bank Indonesia Liquidity Assistance case based on Law Number 10 of 1998 concerning Banking related to the Supreme Court Decision Number 1555 K/Pid.Sus/2019 is through the MSAA mechanism with Release and Discharge clauses and MRNIA, but in reality this has implications for various irregularities by the obligor or the BLBI receiving banks. In order to recover the state financial loss of Rp. 108 trillion to the State treasury, the government uses a civil lawsuit on the basis of the Asset Confiscation Law.